THE USE OF FOLKLORE TO IMPROVE THE STUDENT’S READING COMPERHANSION OF NARRATIVE TEXT - Tria Miranda; Lustina Anggraini; Filya Filya (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This research paper explores the use of folklore to enhance students' reading comprehension of narrative texts in English language learning. The study highlights the challenges faced by Indonesian students in mastering English, with low proficiency levels reported in the EF English Proficiency Index. The paper proposes the "suggestopedia method" as a solution, which utilizes positive suggestions and a relaxed learning environment to improve students' engagement and comprehension. The study emphasizes the use of Indonesian folklore as a valuable resource, citing examples like the legend of MalinKundang, to create a culturally relevant and engaging learning experience. By incorporating folklore into the curriculum, the researchers aim to increase students' enthusiasm, understanding, and enjoyment of reading, ultimately contributing to their overall English language proficiency